Solution of general TPBVP's in optimal control using the sensitivity method - Mercanköşk, Güven. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1983., 1983)
In this thesis, general TPBVP's in Optimal Control have been analyzed using the sensitivity method. A solution method, which uses the trajectory sensitivities to solve general TPBVP's, is developed. Existence of the solutions for the boundary value problems with linear boundary conditions is also studied. The proposed method allows us to parametrize the boundary conditions. If the analytic expressions for the parametric functions are not available then it determines their numerical values. In this way, the method easily converts the original problem into an initial value problem. Then by changing the parameters and using the trajectory sensitivities, it calculates the true parameter values that satisfy the problem constraints, hence finds a solution for the given problem.
Keywords: Control theory.; Sensitivity theory (Mathematics)